IN VITRO PROPAGATION AND FLOWERING FROM NODAL EXPLANTS OF RUMEX VESICARIUS L. – AN IMPORTANT MEDICINAL PLANT - NANDINI B.P.; SUDARSHANA M. S; SHERIEF M. U; NIRANJAN M. H (International Journal of Pharma and Bio Sciences, 2013)
An attempt was made to develop efficient protocol for micropropagation of Rumex vesicarius. Multiple shoots and in vitro flowering was established from nodal explants of Rumex vesicarius. Maximum number of multiple shoots (4 ±1.5) were obtained from nodal explants on MS medium supplemented with BAP (8.8 µM) and NAA (2.4µM). In vitro flowering was also observed within 20 days from nodal culture. For in vitro flowering BAP, NAA and GA3 were used in the concentration of 8.8 µM, 2.4 µM and 1.4 µM respectively. In vitro derived shoots when transferred to half strength MS medium supplemented with IBA (2.4µM) initiated rooting. Maximum number of roots (4±0.57) were obtained on half strength MS medium containing Kn (9.2 µM), IBA (2.4 µM) supplemented with 1.5% activated charcoal. Rooted plants were hardened and transferred to green house conditions with 80% survivability. An efficient protocol for in vitro multiple shoots and flowering from nodal explants of R. vesicarius has been achieved, which is simple and effective tool for the mass propagation and conservation.